Importance of neologisms in medical education - Placencia-Ibadango, Martha Verónica; Vargas-Vera , Ramón Miguel; Vargas-Silva, Kathiuska Steffany; Placencia-Ibadango, Silvia Maribel; Vargas-Silva, Kalid Stefano (Revista Minerva, 2023)
Neologisms are expressions and words that do not traditionally exist in a language, and that are frequently used in medical language. The advance of medicine contrasts with stigmas of dehumanization in professional practice and in doctor-patient communication. Objective: To contrast the importance of neologisms in medical education. Methods: A systematic review was conducted, which used Google scholar, Scopus, Embase, Clinical key, Web of Science as sources of information for articles published between 2014 and 2023. The search was based on keywords. Results: From the content analysis of the selected articles, neologisms were identified in nine main themes: Pedagogy, COVID, History, Anatomy, General Medicine, Pharmacy, Medical Informatics, Veterinary, Dermatology Conclusions: It was determined that the teaching of neologisms favors doctor-patient communication; which represents a positive impact on effective communication.